Misaligned values in software engineering organizations. Issue 3 (4th December 2018) - Lenberg, Per; Feldt, Robert; Wallgren Tengberg, Lars Göran
Abstract: The values of software organizations are crucial for achieving high performance; in particular, agile development approaches emphasize their importance. Researchers have thus far often assumed that a specific set of values, compatible with the development methodologies, must be adopted homogeneously throughout the company. It is not clear, however, to what extent such assumptions are accurate. Preliminary findings have highlighted the misalignment of values between groups as a source of problems when engineers discuss their challenges. Therefore, in this study, we examine how discrepancies in values between groups affect software companies' performance. To meet our objectives, we chose a mixed method research design. First, we collected qualitative data by interviewing fourteen ( N = 14) employees working in four different organizations and processed it using thematic analysis. We then surveyed seven organizations ( N = 184). Our analysis indicated that value misalignment between groups is related to organizational performance. The aligned companies were more effective, more satisfied, had higher trust, and fewer conflicts. Our efforts provide encouraging findings in a critical software engineering research area. They can help to explain why some companies are more efficient than others and, thus, point the way to interventions to address organizational challenges.